2020
DOI: 10.1088/2053-1591/ab715e
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II) and Gd(III) doped boehmite nanostructures: a comparative study of electrical property and thermal stability

Abstract: The present article reports the effect of transition (Cu 2+ ) and rare earth metal (Gd 3+ ) ion doping on structural, microstructural and electrical properties of boehmite nanoparticles. Rietveld refinement is adopted here to refine the x-ray diffractograms for further analyzing the microstructural details and their alteration due to the incorporation of foreign cations. This is probably the first time when dielectric properties of these doped boehmite samples having been reported herein. These samples show re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
3
2
1
Order By: Relevance
“…9015088 (crystallographic open database), which shows the absence of any undesired diffraction maxima revealing the phase purity of the material. 45 It is also observed that the experimental data fitted quite well (fitting coefficient, χ 2 = 1.59) with the theoretical data confirming the curve fitting to be reasonable (Table 1). The refined diffractogram along with the experimental data and the difference plot are depicted in FTIR spectroscopy was performed using a FTIR-8400S, Shimadzu in the wave number ranges between 400 and 4000 cm −1 to get an idea of the coexistence of cdots and boehmite in the synthesized sample.…”
Section: Resultssupporting
confidence: 73%
“…9015088 (crystallographic open database), which shows the absence of any undesired diffraction maxima revealing the phase purity of the material. 45 It is also observed that the experimental data fitted quite well (fitting coefficient, χ 2 = 1.59) with the theoretical data confirming the curve fitting to be reasonable (Table 1). The refined diffractogram along with the experimental data and the difference plot are depicted in FTIR spectroscopy was performed using a FTIR-8400S, Shimadzu in the wave number ranges between 400 and 4000 cm −1 to get an idea of the coexistence of cdots and boehmite in the synthesized sample.…”
Section: Resultssupporting
confidence: 73%
“…Crystallographic size decreases as Gd concentration increases which reveals well dispersion of the Gd NPs [ 38 ]. The obtained XRD planes matches with the JCPDS file No 71-0383 and the reported literatures [ 39 , 40 ]. The d-spacing of the respective peaks/planes, average particle size, and crystallinity are calculated using Debye-Scherrers formula ( Eq.…”
Section: Resultssupporting
confidence: 85%
“…Estimates of the removal efficiency of chromium ions from the solution are comparable with the data in [36] and amount to 30-65%. It is lower than the values obtained in [23,37] (80-85%), which can be associated with the different nature of the doping agent (Cu(II), Gd(III)).…”
Section: Resultscontrasting
confidence: 66%
“…There are known works on doping boehmite with Au, Fe, Ga, Gd, Cr, Cu, Tb, and Eu. [12][13][14][15][16][17][18][19][20][21][22][23][24] The introduction of lanthanides imparts luminescent and optical properties to boehmite. [15,17,20] It was established that the introduction of small amounts (up to 1-3%) of DOI: 10.1002/crat.202100117 gallium, gadolinium, and copper leads to an increase in the specific surface area and pore volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation